Patient Suicide: The Experience of Flemish Psychiatrists - Inês Rothes (2013)
The experience of the most distressing patient suicide on Flemish psychiatrists is described. Of 584 psychiatrists, 107 filled a self-report questionnaire. Ninety-eight psychiatrists had been confronted with at least one patient suicide. Emotional suffering and impotence were the most common feelings reported. Changes in professional practice were described and included a more structured approach to the management of suicidal patients. Colleagues and contact with the patient's family were the most frequently used sources of help, whereas team case review and colleagues were rated as the most useful ones. Patient suicide leads to emotional suffering and has a considerable professional impact.